Using Community Engagement Studios to Increase Recruitment and Retention of Under‐Resourced Participants in Aging Research. (20th December 2022) - Person, Elisa; Orellana, Minerva; Myers, Peter; Foster, Erin; Campbell, Meghan; Mozersky, Jessica; Denny, Andrea; Clark, Pechaz; Johnson, Charis; Johnson, Charis; Balls‐Berry, Joyce E
Abstract: Background: As the population ages in the United States, the prevalence of many diseases like Alzheimer disease, related dementias, and Parkinson disease disproportionately affect those already at greatest risk for premature morbidity and mortality. Aging research has an opportunity to engage and support patients, communities, and caregivers most impacted by these diseases. However, under‐resourced communities frequently lack representation in research, causing decreased generalizability of study results and health inequities among these communities. Methods: Using a community and patient engaged framework, we conducted three community engagement studios (studios) with caregivers, patients, providers, researchers, and advocates from the St. Louis community. The studios provide community input and recommendations on project feasibility, design, and cultural appropriateness. Proposed projects were presented during each studio, followed by a facilitated discussion with a neutral facilitator. Themes were derived using traditional qualitative content analysis. Results: Stakeholders included under‐resourced community members, LGBTQIA+ participants, and those without/inadequate health insurance. The main themes included participant commitment to health, culturally appropriate research design, and incentives. In addition, participants desired collaboration between researchers and the community, including connecting with local Alzheimer's Disease Associations, faith‐based groups, and philanthropic organizations. Conclusion: Our community stakeholders provided feedback on how we could modify the research design to increase community involvement, enhance participant recruitment and commitment, and reach populations currently underrepresented in aging research, especially Alzheimer's disease. The early inclusion of stakeholders in research design and implementation constitutes a preliminary step to building trust within under‐resourced communities and increasing the recruitment and retention of diverse populations.